Magma : a novel - Þóra Hjörleifsdóttir, 1986- (Black Cat, 2021)
"Twenty-year-old Lilja is in love. As a young university student, she is quickly smitten with the intelligent, beautiful young man from school who quotes Derrida and reads Latin and cooks balanced vegetarian meals. Before she even realizes, she's moved in with him, living in his cramped apartment, surrounded by sour towels and flat Diet Cokes. As the newfound intimacy of sharing a shower and a bed fuels her desire to please her partner, his quiet and pervasive manipulations start to unravel her. In an era of pornification, his acts of nearly imperceptible abuse continue to mount as their relationship develops. Lilja wants to hold onto him, take care of him and be the perfect lover. But in order to do so, she gradually lets go of her boundaries and concurrently starts to lose her sense of self. With astounding clarity and restraint, Hjörleifsdóttir sheds light on the commonplace undercurrents of violence that so often go undetected in romantic relationships. She deftly illustrates the failings of our culture in recognizing symptoms of cruelty, and in powerful, poetic prose depicts the unspooling of a tender-hearted woman desperate to love well"--